KEPASTIAN HUKUM HAK RESTITUSI TERHADAP KORBAN TINDAK PIDANA PERDAGANGAN ORANG (TPPO) BERDASARKAN UNDANG-UNDANG NOMOR 21 TAHUN 2007 (Penelitian di Wilayah Hukum Pengadilan Negeri Banda Aceh) - Rosnawati, Mohd. Din, Mujibussalim. (Jurnal Ilmu Hukum, 2016)
Abstract: Article 48 (1) of the Act Number 21/ Year 2007 on Eradication of Human Trafficking (the Act of PTPPO abbreviated in bahasa), states that every criminal-victim of human trafficking, him-/herself as a person or his/her heir is entitled to restitution”. In adjunction to that, verse (3) states “restitution can be granted and worded in a court decision in terms of human trafficking cases”. The objective of this research is to know and to explain the certainty of restitution right towards human trafficking victims. The act regarding the restitution rights has been guaranteed and eligible for human trafficking victims. However, the implementation of Act Number 21/ Year 2007 (or referred as PTTPO) has not yet been fulfilled and there has been no enforcement of it in many cases handled at the First Level Court of Banda Aceh from 2012 until 2014. This can be observed from the legal decision made by the court regarding the human trafficking victims. A legal enforcement of the Act should not be merely stipulated on the written forms or merely in article but this must be applied as concrete actions as well. So far, it has been only written and no strong enforcement of the law in the reality. Therefore, there will be no concrete results. This study recommends that the intended authorities should produce implementation rule regarding the mechanisms or procedures in enforcing the Act and in securing the victims’ right, so that this can be useful for the victims.Keywords: Human Trafficking, Indonesian Law, Legal Enforcement, Restitution Right.Abstrak: Pasal 48 ayat (1) Undang-Undang Nomor 21 Tahun 2007 Tentang Pemberantasan Tindak Pidana Perdagangan Orang (UU PTPPO), menyebutkan “setiap korban perdagangan orang atau ahli warisnya berhak memperoleh restitusi”. Selanjutnya ayat (3) menyebutkan “restitusi tersebut diberikan dan dicantumkan sekaligus dalam amar putusan pengadilan tentang perkara tindak pidana perdagangan orang.” Tujuan dari penelitian ini adalah untuk mengetahui dan menjelaskan tentang kepastian hukum hak restitusi terhadap korban tindak pidana perdagangan orang. Undang-undang telah menjamin adanya kepastian hukum terhadap pemberian hak restitusi bagi korban TPPO. Namun, hak restitusi terhadap korban TPPO dari perkara TPPO yang ada di wilayah hukum Pengadilan Negeri Banda Aceh selama tahun 2012 s.d 2014 belum mencerminkan “kepastian hukum”. Hal demikian dapat dilihat dari putusan perkara TPPO yang telah mempunyai kekuatan hukum tetap. Kepastian hukum dari pasal tersebut bukan hanya tertulis dalam bentuk tulisan atau dalam suatu pasal, tetapi juga harus diterapkan sebagai peristiwa konkrit. Sejauh ini, pasal ini hanya tertulis saja dan belum ada penerapannya dalam kenyataannya. Sehingga, tidak akan ada hasil yang jelas. Studi ini menyarankan kepada pihak berwenang untuk membuat peraturan pelaksana mengenai mekanisme atau prosedur tentang penerapan pasal tersebut demi menjamin hak restitusi korban, sehingga dapat bermanfaat terhadap korban TPPO.Kata kunci : Perdagangan orang, hukum Indonesia, kepastian hukum, hak restitusi.